The Performance of Private Equity Funds - Phalippou, Ludovic; Gottschalg, Oliver (Review of Financial Studies, 2009)
[The performance of private equity funds as reported by industry associations and previous research is overstated. A large part of performance is driven by inflated accounting valuation of ongoing investments and we find a bias toward better performing funds in the data. We find an average net-of-fees fund performance of 3% per year below that of the S&P 500. Adjusting for risk brings the underperformance to 6% per year. We estimate fees to be 6% per year. We discuss several misleading aspects of performance reporting and some side benefits as a first step toward an explanation]